Experiencias metodológicas de una investigación. (2021)
Qualitative investigation may be predominant when in the social investigation, but non excluding the quantitative approach. Its force and its validation criteria are in the interpretative possibility of a reality that emerges from the possibility of constructing and reconstructing sense horizons. The complexity out of proposes the alternatives for the relations among different concepts and social practices.